1993
DOI: 10.1007/bf01956160
|View full text |Cite
|
Sign up to set email alerts
|

Ear disease is not a common complication in cystic fibrosis

Abstract: Although upper respiratory tract involvement is a common finding in cystic fibrosis (CF), there is no agreement on whether hearing is affected in these patients. We studied 75 CF subjects and 50 healthy age-matched children with the same audiological protocol. An original scoring system was used to quantify the degree of hearing involvement (normal, mild, moderate and severe) in each subject. Prevalence of ear involvement in children with CF was similar to that in age-matched control subjects (25.4% and 18% re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

1996
1996
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 6 publications
0
5
0
1
Order By: Relevance
“…Interestingly, there is no correlation of deafness in persons with dysfunctional CFTR (cystic fibrosis) [37,38] and no reports of vertigo in this population. Our results with vestibular tests of CFTR knockout mice are consistent with that observation.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, there is no correlation of deafness in persons with dysfunctional CFTR (cystic fibrosis) [37,38] and no reports of vertigo in this population. Our results with vestibular tests of CFTR knockout mice are consistent with that observation.…”
Section: Discussionmentioning
confidence: 99%
“…9 The prevalence of aminoglycoside-induced hearing loss in these patients is not well defined, and the reported incidence varies from 0% to 39%. [14][15][16][17][18][19][20][21][22] This wide discrepancy is most likely the result of diverse testing methods (eg, conventional PTA, high-frequency audiometry, and auditory brainstem responses), differences of the populations studied, and varying dosage and du- ration of drug regimens. In our study, conventional PTA thresholds were within normal limits for patients with CF and a history of aminoglycoside intake and remained virtually unchanged following the last gentamicin exposure.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, only 2 studies 17,22 used properly selected control groups (healthy subjects and patients with CF not treated with aminoglycoside), while in 3 other studies only healthy subjects served as a control group. 18,20,21 Unfortunately, the criteria for defining hearing loss were not presented clearly in any of these studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, temporal bone studies of individuals with and without CF have shown similar pneumatization and mucosal histology of the middle ear (Berkhout et al, 2014; Seifert et al, 2010; Todd & Martin, 1988; Yildirim et al, 2000). In addition, several studies have suggested that individuals with CF are at no higher risk than age-matched controls, with some studies showing lower rates of inflammatory ear disease compared to controls (Bak-Pedersen & Larsen, 1979; Cepero et al, 1987; Cipolli et al, 1993; Forcucci & Stark, 1972; Jorissen, De Boeck, & Feenstra, 1998; Martins et al, 2011). However, most previous studies did not include bone conduction audiometry, and if tympanometry was included, individuals with middle ear issues were excluded (otitis media, tympanic membrane perforation).…”
Section: Discussionmentioning
confidence: 99%